A review on several important aspects of the camels - Asad Ali Khaskheli (Syiah Kuala University, 2020)
The present study was conducted to gather the information regarding habitat, population, management, production and economic analysis of the camels worldwide. The main findings of review showed camel population around 25.89 million worldwide in almost 47 countries. Majority of camel herders were reported un-educated. Researchers further indicated that camels generally are reared under sedentary (50%), transhumant (25%), nomadic (15%) and household (10%) management systems. Age of camel famers ranges from 25 to 50 years. The female ratio markedly remains higher than males and young ones because the females are generally used for milk production. However the males are mostly used to carry the luggage, carrying load pulling cart etc. It was also stated by scientists that camels are mostly allowed for open grazing of natural vagetations. Breeding is practiced by natural method and the camel spend 20 to 30 minutes for matting. The female camels reach at the puberty age in 3-5 years, while male at 3.5 to 5.5 years. The duration of estrus cycle in camels vary from 16 to 22 days. Breeding period of camels remain between November and March. The average hair production of camels is 1.63 kg, average daily milk production 6.40 liter. Male have carrying capacity of 553 kg. In conclusion the husbandry practices of camel farming worldwide are based on old traditional methods, however the scientific farming rarely exits. There is no extension services available for the herders to motivate, educate and aware them modern management practices. Market infrastructure, as per study review, is not well established. Mostly the camel herder sale out their animals to middlemen due to long market distances.